Membangun Kesadaran Etika Multikulturalisme di Indonesia - Achmad Charris Zubair (Jurnal Filsafat "WISDOM", 2003)
Indonesian is rich with natural resource, cultures, religions, and tribes. Ethics is required to create mix, but not homogenized society, so that an openess towards the others is of importance requirements. Pancasila which consist of the five princples serves as an umberella for everyone who live in Indonesia in order to live all together.